GANGGUAN OTAK YANG BERKAITAN DENGAN PROSES BELAJAR - M. Fikar; Hakim, Rosniati; Dahlan, Dasrizal; Lahmi, Ahmad (LPPM STAI Muhammadiyah Probolinggo, 2025)
This study explores the relationship between brain disorders and the learning process from the perspective of neuroscience in Islamic education. Highlighting the concepts of intellect and brain based on the Qur'an, it explains how brain function influences human learning ability. The neuroscience approach, particularly in the anatomy of the brain, such as the cerebrum, cerebellum, brainstem, and limbic system, is elaborated to understand the brain's role in learning. Several brain disorders, including Minimal Brain Dysfunction (MBD), dyslexia, dyscalculia, and ADHD, are also described as factors affecting the learning process. Furthermore, this article emphasizes the importance of educators understanding brain functions to optimize neuroscience-based learning. In conclusion, the integration of Islamic education and neuroscience provides new insights into developing more effective learning approaches.